2012
DOI: 10.1016/j.rbp.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicide risk and comorbidities in postpartum women in Pelotas

Abstract: Lower education levels and psychiatric disorders are associated with suicide risk. Bipolar disorder is the psychiatric disorder with the highest impact on suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 44 publications
5
49
2
2
Order By: Relevance
“…The results of this study are consistent with previous research where the prevalence of comorbid postpartum depressive symptomatology and anxiety in the first year postpartum ranged between 3% and 10% (Adewuya and Afolabi, 2005;Giakoumaki et al, 2009;Miller et al, 2015) and that of clinically defined comorbidity ranged between 2% and 13% (Austin et al, 2010;Reck et al, 2008;Tavares et al, 2012a). Women with postpartum depressive symptomatology are also more likely to experience anxiety postnatally than women without any depressive symptomatology (Reck et al, 2008;Zietlow et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study are consistent with previous research where the prevalence of comorbid postpartum depressive symptomatology and anxiety in the first year postpartum ranged between 3% and 10% (Adewuya and Afolabi, 2005;Giakoumaki et al, 2009;Miller et al, 2015) and that of clinically defined comorbidity ranged between 2% and 13% (Austin et al, 2010;Reck et al, 2008;Tavares et al, 2012a). Women with postpartum depressive symptomatology are also more likely to experience anxiety postnatally than women without any depressive symptomatology (Reck et al, 2008;Zietlow et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Currently, routine strategies for the identification of both postpartum depression and anxiety is not universally recommended. However, a study showed that women with comorbidities of depression and an anxiety disorder have 17-fold higher risk for suicide than women who do not suffer from any mood disorder (Tavares et al, 2012b).…”
Section: Psychosocial Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of postpartum studies focused on birth as the traumatic event (25 studies out of 28). The remaining studies looked at postpartum PTSD related to any event (Grigoriadis et al, 2011;Tavares et al, 2012;Wenzel et al, 2005). The 59 studies originated from 23 countries, including European nations, UK, USA, Canada, Australia, Brazil, South Africa, Nigeria and Tanzania, Turkey, Greece, Malaysia, Iran and Israel.…”
Section: 1study Characteristicsmentioning
confidence: 99%
“…Additionally, studies have previously reported that supportive therapeutic interventions by non-medical workers adequately address symptoms of depression, especially around the post-partum period (McComish JF, Groh CJ, & Moldenhauer JA, 2013). This period is marked by an increased risk of developing major depression and similar serious mood disorders (Di Florio A et al, 2013; Tavares D et al, 2012; Topiwala A, Hothi G, & Ebmeier KP, 2012). …”
Section: Discussionmentioning
confidence: 99%